2021
DOI: 10.3390/horticulturae7060130
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glutathione-Ascorbate Cycle and Photosynthetic Electronic Transfer in Alternative Oxidase-Manipulated Waterlogging Tolerance in Watermelon Seedlings

Abstract: Alternative oxidase (AOX) has been documented to mitigate the oxidative stress caused by abiotic stresses. However, it remains unknown how AOX regulates the antioxidant system and photosynthesis under waterlogging. To address this issue, we used two watermelon (Citrullus lanatus L.) cultivars (waterlogging tolerant cultivar ‘YL’ and sensitive cultivar ‘Zaojia8424’) as materials and the AOX inhibitor salicylhydroxamic acid (SHAM) to investigate the effects of AOX on photosynthesis and reactive oxygen species me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…SOD, CAT, and POD are the primary antioxidant enzymes involved in the antioxidant defense system, in which SOD catalyzes the conversion of O −2 into H 2 O 2 , and POD and CAT catalyze the reduction of H 2 O 2 to H 2 O and O 2 [47]. In general, plants increase the activities of various antioxidant enzymes to cope with water stress [48][49][50]. In our study, higher MDA content and EL levels at up to 60% SMC and at 120% SMC suggested that both water deficit and waterlogging stress accelerated membrane lipid peroxidation and damaged cell membrane stability (Figure 3), which agreed with previous findings indicating that prolonged drought or waterlogging stress disturbed antioxidant metabolism and ROS homeostasis [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…SOD, CAT, and POD are the primary antioxidant enzymes involved in the antioxidant defense system, in which SOD catalyzes the conversion of O −2 into H 2 O 2 , and POD and CAT catalyze the reduction of H 2 O 2 to H 2 O and O 2 [47]. In general, plants increase the activities of various antioxidant enzymes to cope with water stress [48][49][50]. In our study, higher MDA content and EL levels at up to 60% SMC and at 120% SMC suggested that both water deficit and waterlogging stress accelerated membrane lipid peroxidation and damaged cell membrane stability (Figure 3), which agreed with previous findings indicating that prolonged drought or waterlogging stress disturbed antioxidant metabolism and ROS homeostasis [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the AOX pathway can dissipate excessive chloroplastic reducing equivalents and balancec photosynthetic electron transport (Jiang et al 2019, Challabathula et al 2022. Several studies have demonstrated that the photosynthetic rate and PSII photochemical efficiency obviously decrease and that the photosynthetic electron transport chain was more overreduced in AOX-deficient mutants and salicylhydroxamic acid (SHAM, AOX inhibitor)-treated leaves under abiotic stresses (Giraud et al 2008, Yoshida et al 2011, Dahal and Vanlerberghe 2018, Zheng et al 2021, Challabathula et al 2022. AOX overexpression in tobacco was shown to improve photosynthetic performance compared with the wild type under drought conditions (Dahal et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…AsA is not synthesized by chloroplast, but AsA mostly accumulates in this organelle. It is evident that this molecule is implicated in events related to light capture and electron transport by photosynthetic pigments, the AsA-GSH cycle in chloroplast, and other processes ( Yabuta et al., 2007 ; Nunes-Nesi et al., 2008 ; Zheng et al., 2021 ). On the other hand, there are data showing that AsA accumulates in mitochondria at lower concentrations than in chloroplasts ( Zechmann et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%